Peran Penting Komunikasi Bisnis Antarbudaya Dalam Era Globalisasi - Eko Purnomo; Fitri Annisa; Nabila Syafitri; Muhammad Lutfi; Suhairi Suhairi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Globalization has created business opportunities that are expanding worldwide. In this increasingly connected business environment, intercultural communication is very important. Cultural differences which include language, values, norms, and beliefs affect the way people interact and do business. This article will discuss the background and importance of intercultural business communication in the era of globalization. This study analyzes the impact of globalization on business and identifies intercultural communication challenges that organizations face. Furthermore, this article discusses the benefits of developing intercultural communication competencies and strategies that can be used to enhance effective communication between different cultures.